Model Pembelajaran PBL Dipadu Strategi NHT Untuk Memotivasi dan Meningkatkan Hasil Belajar Peserta Didik - Hardianti, Hardianti; Copriady, Jimmi; Haryati, Sri (Program Pasca Sarjana UNM, 2020)
This study aims to increase learning motivation and results student learning through the application of the PBL learning model combined with the NHT strategy on the subject of stoichiometry at MAN 1 Pekanbaru. The population in this study is all students of class X MIA, amounting to four classes. Normality test use Liliefors test which aims to see whether the data used have a normal distribution and homogeneity test using the variance similarity test and test average similarity which aims to see whether the sample used is already homogeneous. Sampling is done by the cluster random sampling method obtained by two classes namely class X MIA 1 as a control class and class X MIA 4 as an experimental class. The results of testing the hypothesis using the t-test showed that there are significant differences between the control class and the experimental class on learning motivation and learning outcomes. Where is learning motivation and results learning experimental class students higher than students in the class control. Determination of the relationship of learning motivation to student learning outcomes done with a person correlation test that shows the existence of a relationship between learning motivation towards learning outcomes of students in the class applied PBL learning models combined NHT strategies on the subject of stoichiometry at MAN 1 Pekanbaru with a strong positive correlation category.